2015
DOI: 10.1016/j.celrep.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Regulation of Synaptic Plasticity at Striatopallidal and Striatonigral Neurons Orchestrates Motor Control

Abstract: The basal ganglia play a critical role in shaping motor behavior. For this function, the activity of medium spiny neurons (MSNs) of the striatonigral and striatopallidal pathways must be integrated. It remains unclear whether the activity of the two pathways is primarily coordinated by synaptic plasticity mechanisms. Using a model of Parkinson's disease, we determined the circuit and behavioral effects of concurrently regulating cell-type-specific forms of corticostriatal long-term synaptic depression (LTD) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 39 publications
8
54
0
Order By: Relevance
“…It has been speculated that eCB LTD can be induced more reliably at iMSN synapses than dMSN synapses (Kreitzer and Malenka, 2007), and this may depend on induction conditions (Shen et al, 2008; Trusel et al, 2015). This topic has remained controversial despite several reports of LTD occurring in both MSN subtypes (Bagetta et al, 2011; Picconi et al, 2011; Shen et al, 2008; Wang et al, 2006, 2017; Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been speculated that eCB LTD can be induced more reliably at iMSN synapses than dMSN synapses (Kreitzer and Malenka, 2007), and this may depend on induction conditions (Shen et al, 2008; Trusel et al, 2015). This topic has remained controversial despite several reports of LTD occurring in both MSN subtypes (Bagetta et al, 2011; Picconi et al, 2011; Shen et al, 2008; Wang et al, 2006, 2017; Wu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Given that this signaling is restricted to iMSNs, the involvement of iMSN D2Rs in LTD will be restricted to this MSN subtype. A few reports have suggested that this is the case (Kreitzer and Mal-enka, 2005; Shen et al, 2008; Trusel et al, 2015). However, eCB-LTD at synapses onto dMSNs has been observed (Bagetta et al, 2011; Picconi et al, 2011; Shen et al, 2008; Wang et al, 2006, 2017; Wu et al, 2015) and is prevented by the D2R antagonist in these neurons (Bagetta et al, 2011; Wang et al, 2006).…”
Section: Introductionmentioning
confidence: 88%
“…Although these striatal synaptic defects have been proposed to be the cause of repetitive and compulsive grooming behavior in Shank3B mutant mice, direct evidence to support this hypothe- act as retrograde signaling to activate presynaptically located CB1 receptors (CB1Rs) to reduce neurotransmission. However, there is controversy in the literature as to whether the eCB-LTD can be induced at glutamatergic synapses onto both D1 and D2 MSNs because high-frequency electrical stimulation (eHFS) might recruit intrastriatal dopaminergic and cholinergic signaling that can modulate this form of LTD (56)(57)(58)(59)(60). We thus started out to test whether the induction protocol, pairing HFS (4 trains of 100 Hz/s given at 10-second interval) of presynaptic glutamatergic afferent fibers by placing a stimulating electrode at the inner edge of the corpus callosum (instead of intrastriatal stimulation) and postsynaptic depolarization (DP) of MSNs (HFS/DP), was able to induce LTD in both types of MSNs and whether LTD could be blocked by a CB1R antagonist in both types of neurons.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, chemogenetic activation of G s signaling in dSPNs (mimicking ON-state signaling) aggravated dyskinesia [41]. Several other strategies of normalizing aberrant plasticity also improved behavior, further implicating striatal synaptic plasticity in the disease mechanisms [42,43]. …”
Section: Introductionmentioning
confidence: 99%